Functional studies on human γδ T cells and their interactions with dendritic cells and B cells - Petrasca, Andreea (Trinity College (Dublin, Ireland). Department of Immunology, 2016)
γδ T cells are innate T cells that play central roles in protection against microorganisms and cellular stress. There are three main subsets in humans: Vδ1, Vδ2 and Vδ3 T cells. The most abundant of these, Vδ2 T cells, recognises phosphoantigens produced in one of two pathways of isoprenoid synthesis, a cellular metabolic pathway employed by all eukaryotes and many bacteria. This allows Vδ2 T cells to monitor for infection and tumour transformation which result in altered cellular concentration of phosphoantigens. Vδ1 and Vδ3 T cells are predominantly found in epithelial tissues and play roles in homeostasis, tissue integrity and lipid surveillance and are found at increased frequencies in some patients with tumours and viral infections. Upon activation, γδ T cells can kill target cells and rapidly promote adaptive immune responses through physical interactions with other immune cells, and rapid and selective secretion of T helper type 1 (TH1), TH2, TH17 and regulatory cytokines. In the present study we carried out a phenotypic and functional comparison of the three γδ T cell subsets in human peripheral blood and examined methods for generating lines of Vδ2 and Vδ3 T cell for functional characterisation. We found that stimulation with the phosphoantigen (E)-4-Hydroxy-3-methyl-but-2-enyl pyrophosphate (HMB-PP) and interleukin-2 yielded highly pure populations of Vδ2 T cells capable of producing TH1 and TH2 cytokines upon re-stimulation. In contrast, treatment with the aminobisphosphonate zoledronate, which promotes isoprenoid synthesis, resulted in expansion of Vδ2 T cells that produced TH2 cytokines only. In the absence of a known ligand for Vδ3 T cells, we used the T cell mitogen phytohaemagglutinin to stimulate sorted Vδ3+ cells which resulted in up to 1,000-fold expansion within 3-4 weeks. We next examined the reciprocal activating interactions between Vδ2 T cells, dendritic cells (DC) and B cells in co-culture experiments and defined the resulting cytokine profiles, cell phenotypes and antibody responses and the molecular interactions involved. We found that Vδ2 T cells promoted maturation of DC into antigen-presenting cells capable of stimulating TH1 cell responses. In contrast, Vδ2 T cells promoted differentiation of B cells into antibody-secreting plasma cells with phenotypes of antigen-presenting cells, but which produced TH2 cytokines. While co-stimulatory molecules, TH1 cytokines and cell contact were required for DC maturation by Vδ2 T cells, they did not play major roles in B cell maturation. The present study investigated, for the first time, the relationship between Vδ3 T cells and B cells and revealed that while Vδ3 T cells induced co-stimulatory marker expression by B cells, they failed to induce significant cytokine or antibody secretion. However, activated B cells were able to induce IL-17 secretion by Vδ3 T cells. We also assessed the ability of Vδ3 T cells to recognise CD1 molecules, but found that freshly-isolated or expanded Vδ3 T cells showed no reactivity against CD1a, CD1b, CD1c or CD1d molecules in the presence or absence of a number of glycolipids. Since Clostridium difficile appears to utilise the non-mevalonate pathway of isoprenoid biosynthesis, suggesting that it can produce HMB-PP, we assessed the ability of HMB-PP to stimulate proliferation and cytokine secretion by Vδ2 T cells. We found, in spite of great inter-donor variability, C. difficile secreted a Vδ2-stimulating agent which induced T cell proliferation and cytokine production in most donors and was comparable to the stimulating capabilities of HMB-PP. However, the identity of this secreted factor remains to be elucidated. These findings highlight the role of γδ T cells in immunosurveillance, innate immunity, antigen presentation and activation of adaptive immunity. Their ability to act as a bridge between innate and adaptive immune responses places these cells as attractive candidates for immunotherapy for infectious and immune-mediated diseases and cancer. γδ T cells are innate T cells that play central roles in protection against microorganisms and cellular stress. There are three main subsets in humans: Vδ1, Vδ2 and Vδ3 T cells. The most abundant of these, Vδ2 T cells, recognises phosphoantigens produced in one of two pathways of isoprenoid synthesis, a cellular metabolic pathway employed by all eukaryotes and many bacteria. This allows Vδ2 T cells to monitor for infection and tumour transformation which result in altered cellular concentration of phosphoantigens. Vδ1 and Vδ3 T cells are predominantly found in epithelial tissues and play roles in homeostasis, tissue integrity and lipid surveillance and are found at increased frequencies in some patients with tumours and viral infections. Upon activation, γδ T cells can kill target cells and rapidly promote adaptive immune responses through physical interactions with other immune cells, and rapid and selective secretion of T helper type 1 (TH1), TH2, TH17 and regulatory cytokines. In the present study we carried out a phenotypic and functional comparison of the three γδ T cell subsets in human peripheral blood and examined methods for generating lines of Vδ2 and Vδ3 T cell for functional characterisation. We found that stimulation with the phosphoantigen (E)-4-Hydroxy-3-methyl-but-2-enyl pyrophosphate (HMB-PP) and interleukin-2 yielded highly pure populations of Vδ2 T cells capable of producing TH1 and TH2 cytokines upon re-stimulation. In contrast, treatment with the aminobisphosphonate zoledronate, which promotes isoprenoid synthesis, resulted in expansion of Vδ2 T cells that produced TH2 cytokines only. In the absence of a known ligand for Vδ3 T cells, we used the T cell mitogen phytohaemagglutinin to stimulate sorted Vδ3+ cells which resulted in up to 1,000-fold expansion within 3-4 weeks. We next examined the reciprocal activating interactions between Vδ2 T cells, dendritic cells (DC) and B cells in co-culture experiments and defined the resulting cytokine profiles, cell phenotypes and antibody responses and the molecular interactions involved. We found that Vδ2 T cells promoted maturation of DC into antigen-presenting cells capable of stimulating TH1 cell responses. In contrast, Vδ2 T cells promoted differentiation of B cells into antibody-secreting plasma cells with phenotypes of antigen-presenting cells, but which produced TH2 cytokines. While co-stimulatory molecules, TH1 cytokines and cell contact were required for DC maturation by Vδ2 T cells, they did not play major roles in B cell maturation. The present study investigated, for the first time, the relationship between Vδ3 T cells and B cells and revealed that while Vδ3 T cells induced co-stimulatory marker expression by B cells, they failed to induce significant cytokine or antibody secretion. However, activated B cells were able to induce IL-17 secretion by Vδ3 T cells. We also assessed the ability of Vδ3 T cells to recognise CD1 molecules, but found that freshly-isolated or expanded Vδ3 T cells showed no reactivity against CD1a, CD1b, CD1c or CD1d molecules in the presence or absence of a number of glycolipids. Since Clostridium difficile appears to utilise the non-mevalonate pathway of isoprenoid biosynthesis, suggesting that it can produce HMB-PP, we assessed the ability of HMB-PP to stimulate proliferation and cytokine secretion by Vδ2 T cells. We found, in spite of great inter-donor variability, C. difficile secreted a Vδ2-stimulating agent which induced T cell proliferation and cytokine production in most donors and was comparable to the stimulating capabilities of HMB-PP. However, the identity of this secreted factor remains to be elucidated. These findings highlight the role of γδ T cells in immunosurveillance, innate immunity, antigen presentation and activation of adaptive immunity. Their ability to act as a bridge between innate and adaptive immune responses places these cells as attractive candidates for immunotherapy for infectious and immune-mediated diseases and cancer.
Keywords: Immunology, Ph.D.; Ph.D. Trinity College Dublin